Agreement Law Analysis Renting a Reception Building Wedding During Covid-19 - Andi Winda Kurnia Akbar; Ilham Abbas; Abdul Qahar (Golden Ratio of Law and Social Policy Review (GRLSPR), 2022)
The world today is being shocked by the Corona Virus Disease 2019 (Covid-19) or commonly called the Corona Virus whose status has been determined by the WHO (World Health Organization or World Health Organization) as a Pandemic. That is, it has spread widely in the world. Covid-19 has affected the course of the rental agreement for the wedding reception building. This study uses normative legal research methods, by examining library materials using the object of study in the form of existing literature, both sourced from books, magazines, and regulations that have a correlation with the discussion of problems, so this writing is also library research. The results of this study indicate that Covid-19 can be classified as a relative force majeure, fulfilling unexpected elements, there are obstacles that cause non-performance, there is no bad faith from the debtor, and the debtor cannot be charged with risk. The legal consequence of Covid-19 is a delay in the agreement